2020
DOI: 10.1177/1474515119900062
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience of preheated and room temperature skin disinfection prior to cardiac device implantation: A randomised controlled trial

Abstract: Background: Clinically, patients often comment on the coolness of the skin disinfectant. However, scarce evidence is available regarding patients’ experience during intraoperative skin disinfection. Aims: The aim of this study was to describe and compare intraoperative patient experiences with preheated and room temperature skin disinfectant. Method: This randomised controlled trial included 220 patients undergoing cardiac device implantation. Patients allocated to preheated (36°C) or room temperature (20°C) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, regular cleaning and disinfection can effectively reduce the presence of pollutants and pathogens in the environment, reducing the risk of hospital-acquired infections. [27][28][29][30] This study used the BSSI scale to assess the stress levels of staff, providing a basis for corresponding intervention measures. The results showed that women staff had higher BSSI scores than men, indicating that women are more susceptible to stress in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, regular cleaning and disinfection can effectively reduce the presence of pollutants and pathogens in the environment, reducing the risk of hospital-acquired infections. [27][28][29][30] This study used the BSSI scale to assess the stress levels of staff, providing a basis for corresponding intervention measures. The results showed that women staff had higher BSSI scores than men, indicating that women are more susceptible to stress in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regular cleaning and disinfection can effectively reduce the presence of pollutants and pathogens in the environment, reducing the risk of hospital-acquired infections. [ 27 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…It gives insights in why particular phenomena occur or what underlying mechanisms are 1 . Over the past two years, the European Journal of Cardiovascular Nursing published 20 qualitative studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . These studies used methods such as content analysis, ethnography, or phenomenology.…”
Section: Introductionmentioning
confidence: 99%